A bioeconomic foundation of the Malthusian equilibrium : body size and population size in the long-run - Carl-Johan Dalgaard; Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
This paper develops a bioeconomic Malthusian growth model. By integrating recent research on allometric scaling, energy consumption and ontogenetic growth, we provide a model where subsistence consumption is endogenously linked to body size and fertility. The theory admits a unique Malthusian equilibrium in a two-dimensional state space characterized by population density and body size (metabolic rate) of the representative adult. As a result, the analysis allows us to examine the link between human biology, economic productivity, body size, and population size. Off the steady-state we investigate the possibility of cyclical behavior of the size of a population and the size of its representative member over the very long-run. We also demonstrate that a take-o? into sustained growth should be associated with increasing income, population size and body size. The increase in the latter is, however, bounded and can be viewed as convergence to a biologically determined upper limit.
Keywords: O11; I12; J13; 330; Subsistence; Nutrition; Metabolism; Population Growth; Ontogenetic Growth; Malthus; Bevölkerungstheorie; Ernährung; Lebensstandard; Bioökonomik; Bevölkerungsökonomie; Demographischer Übergang; Theorie